Stepping motors : a guide to theory and practice. - Acarnley, Paul, ....- (London : Institution of Engineering and Technology, 2007)
Outlines the design and operation of stepping motors, particularly hybrid and variable-reluctance motors for computer output devices. Acarnley (University of Newcastle) discusses drive circuits, load positioning, the pull-out torque/speed characteristic, and both open- loop and closed-loop control schemes. The fourth edition updates recent trends.